ANALISIS EFEKTIVITAS DAN EFISIENSI PELAKSANAAN ANGGARAN BELANJA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN KEBUMEN - Mispiyanti Mispiyanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
One important aspect in improving the performance of the regional government is through local development planning policy and sustainable quality. BAPPEDA function and role as one of the local technical institute which is the task of supporting elements of regional heads, to carry three (3) obligatory functions that must be implemented, namely the affairs of spatial planning, development planning and statistical affairs. The government budget related to the process of determining the amount of the allocation of funds for each program and activity monetary terms in the use of funds belonging. . The purpose of this study was to determine the effectiveness and efficiency of budget execution of Kabupaten Kebumen Bappeda in 2011-2014 in terms of the absorption of the budget used by the Agency for implementing program/activities aimed Kabupaten Kebumen public. The results showed that the effectiveness of budget execution Bappeda from 2011 until 2014 is said to be effective despite the volatile situation . Effectiveness of budget shows the percentage of 96.52 % , 94.87 % , 94.06 % , 95.88 % for 4 consecutive years . Direct expenditure budget for the programs also show the overall effective rate . Besides the efficient use of the budget in 2011 to 2014 is also said to be very efficient . Although there is a tendency in each year decreased the level of efficiency Keywords: Effectiveness, Efficient, Budget.